Perencanaan Pembelajaran Berbasis Media Teknologi Untuk Meningkatkan Keterampilan Menyimak Bahasa Inggris (Studi Kasus Siswa Level 3 Rumah Belajar Edukita Kota Bandung) - Suharyanto H. Soro; Maman Suherman; Pina Dewi Apiyanti; Dadan Budiman (LP. Ma'arif Janggan Magetan, 2024)
English language learning in educational units has experienced many failures. One factor is the preparation of plans that are not in accordance with the reality in the field. Planning is carried out by considering internal and external elements of the school so that in its implementation it runs smoothly and the goals are achieved. The purpose of this study is to analyze and describe how planning is carried out, the strategies applied, the challenges faced, and their impact on student competence. The researcher used a case study approach with a qualitative research paradigm. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive analysis model. Sampling was carried out by purposive sampling. In other words, the sample in the study: edukita partners, class assistants, level 3 students. The number of samples was 25 people. The results of the study showed that learning planning involved collaboration between native teachers and local tutors, with a focus on integrating global insights with local contexts. The strategies implemented include synchronous learning through platforms such as Zoom and Google Meet, asynchronous access to digital modules, and gamified learning using interactive applications such as Quizizz. This approach utilizes technology to create a flexible and engaging learning environment. Challenges include technical limitations (internet access), cultural differences, digital literacy gaps among students, and different teaching methods. To address these, solutions such as technology training, provision of offline materials, and cultural orientation for native teachers have been implemented. Integrating technology with collaboration between native teachers significantly improves students' listening skills, digital literacy, and fosters multicultural understanding.